2019
DOI: 10.1177/2325967119s00284
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Growth Factors, Cytokines and Chemokines in Bone Marrow Concentrate and Platelet Rich Plasma: A Prospective Analysis

Abstract: Objectives: Autologous platelet-rich plasma (PRP) and bone marrow concentrate (BMC) are orthobiologic therapies with numerous growth factors and cytokines. Mesenchymal stem cells (MSCs) are also present in BMC; however, comprise a very limited component of the available monocytes. Other clinically relevant factors and cytokines, including interleukin-1 receptor antagonist (IL-1Ra), are implicated in the anti-inflammatory and regenerative processes. Prior to optimizing the clinical utility of PRP and BMC as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…LP-PRP was tested since lower concentrations of leukocytes is less likely to induce excessive inflammation and fibrosis after an LP-PRP intra-articular injection [ 21 , 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LP-PRP was tested since lower concentrations of leukocytes is less likely to induce excessive inflammation and fibrosis after an LP-PRP intra-articular injection [ 21 , 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mix-species TGF-β magnetic bead panel (EMD Millipore Corp, Billerca, MA, USA) used were to measure TGF-β1 concentrations. A standard manufacturer’s protocol for the Luminex ® 200 system (Luminex Corp, Austin, TX, USA) multiplex instrument was utilized as previously published [ 47 ]. All reagents were prepared and stored according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The use of a more patient-specific PRP, with specific cytokines or growth factors knocked out for treating different knee conditions, may better direct the biological healing potential of PRP for different pathologies such as meniscal healing, articular cartilage resurfacing, and patellar tendinopathy. 8 Although the present study could certainly be demonstrated by others to be valid in future studies, there are some points that need to be addressed in biologics research to ensure that we are providing the best care for our patients. Among other essential criteria described by the minimum information for studies evaluating biologics in orthopedics guidelines, the methods of PRP preparation and the product components (platelets, leukocytes, and red cells) with their respective concentrations were not reported in the present study by Berdis et al Thus, others cannot duplicate this study as it is presented.…”
Section: See Related Article On Page 3107mentioning
confidence: 75%
“…Also, a clinical study directly comparing LR- and LP-PRP shown no clinical difference in outcome after 12 months [ 23 ]. LR-PRP contains more proinflammatory molecules and a higher concentration of growth factors but also a higher concentration of anti-inflammatory cytokines like interleukin 1 receptor antagonist (IL1-Ra) [ 64 ]. Newer studies describe the process of “inflammatory regeneration” with the secretion of both pro- and anti-inflammatory cytokines by the leukocytes, showing positive effects on tissue regeneration [ 42 ].…”
Section: Discussionmentioning
confidence: 99%